Pengaruh Kualitas Pelayanan Fiskus dan Kesadaran Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Relawan Pajak Sebagai Variabel Moderasi - Aras, Ainul Karima; Lince Bulutoding; Della Fadhilatunisa (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to examine the effect of the quality of tax authorities' services on individual taxpayer compliance, examine the effect of tax awareness on individual taxpayer compliance, test tax volunteers able to moderate the relationship between the quality of tax authorities' services and individual taxpayer compliance, and test tax volunteers able to moderate the relationship between tax awareness and individual taxpayer compliance. This research is a type of quantitative research with a quantitative descriptive approach. The location in this study is the Sungguminasa Tax Counseling and Consultation Service Office. The sample in this study was 150 with two sample criteria, namely the first taxpayer who has experienced the services of a tax volunteer and the second taxpayer who does not know how to report the Annual Tax Return (SPT). The data used is the type of primary data obtained through the distribution of questionnaires.